İTİRAZ EDİLMEYEN FATURANIN MALIN TESLİM EDİLMİŞ VE İŞİN YAPILMIŞ OLDUĞUNU GÖSTERİP GÖSTERMEYECEĞİ - (:unkn) unknown (My University, 2016)
eTTK-1956 m. 23/f.1 (TTK. m. 21/no.1) hükmüne dayanılarak itiraza uğramayan faturanın, konusu olan malın teslim edildiğini, işin yapılmış olduğunu da göstereceği ileri sürülmüştür. Bugün de sözleşmenin ifası ile ilgili bir belge olan faturanın, itiraza uğramaması üzerine, istisnaî haller dışında sözleşmenin ifa edildiğini göstereceği savunulur. TTK. m. 21/no.1'e göre faturanın geçerliliği ya da hukuki sonuçlar doğurabilmesi için, geçerli bir sözleşmeye dayanılarak düzenlenmiş olması şarttır. Yoksa, faturaya itiraz edilmemiş olması, sözleşmenin varlığını göstermez. TTK. m. 21/no.2 hükmündeki karine de faturaya yazılması olağan olan içerik bakımındandır. Şu halde; süresi içinde faturaya itiraz edilmemekle birlikte, uyuşmazlık söz konusu ise, sözleşmenin varlığını ve kural olarak, malın teslim edildiğini, işin görüldüğünü, diğer bir menfaatin sağlandığını ispat yükü, bu hususları iddia eden konumundaki faturayı düzenleyip gönderen taraf üzerindedir (TMK. m. 6; HMK. m. 190/no.1).

It's been alleged that according to repealed Turkish Commercial Code dated 1956 art. 23/1 (current Turkish Commercial Code art. 21/no. 1), an invoice which has not been objected to, shows that the goods in question have been delivered and/or the work in question has been performed. Even today it's defended that a not-objected invoice, which is a document relating to the execution phase of the contractual relationship, showsapart from some exceptional circumstancesthat the obligations arising from the contract have been fulfilled. According to the Turkish Commercial Code (TCC) art. 21/no. 1, for an invoice to be valid or to have legal consequences, it's conditioned that the invoice is issued based on a valid contract. Otherwise, not objecting to an invoice doesn't prove the existence of any contract. Accordingly, the presumption made in TCC art 21/no. 2 is related to the ordinary content of the invoice. Therefore, even though the objection to the invoice wasn't made in due time, in the event of a dispute, the burden of proof about the existence of contract and in principle delivery of goods, performing of the work or affording of another interest, is up to the issuer/sender of the invoice who'd be also in position of claimant (Turkish Civil Code art. 6; Civil Code of Procedure art. 190/no. 1).
Whether an Invoice Which Has Not Been Objected to Shows That The Goods in Question Have Been Delivered and/or The Work in Questıon Has Been Performed
Keywords: Hukuk